KEDUDUKAN SENTANA RAJEG DALAM HARTA BERSAMA - Ratmini, Ni Ketut Sri (Institut Hindu Dharma Negeri Denpasar, 2020)
In customary law, the issue of heredity is included in the scope of kinship law, so the issue of sentana rajeg will not be separated from the discussion about the kinship system adopted by the Balinese people. The traditional Balinese people adhere to the patrilineal or fatherly kinship system which is better known in the community as the kepurusa or purusa line. The goal in the family life of the Balinese people is to have children. Associated with the sex of the child (descendant), it is expected that the descendant of a boy. Balinese customary law which is patrilineal has a strong influence on the value of the child (descendant), that is, boys have a higher value than girls. If a family only has daughters, efforts will be made to increase their status to male, namely by adopting the girl as sentana rajeg by means of merry marriage.The problem studied is the position of Sentana Rajeg in the formation of joint assets. This paper aims to examine from a legal and gender perspective the position of Sentana Rajeg in the formation of collective assets, using the literature review method. From the results of a study of several literature, it can be seen that Sentana Rajeg has an important position in contributing to the formation of collective assets. This is because Sentana Rajeg is an heir who gets an inheritance from his parents and the results of the management of the inheritance can be used to form joint assets. In addition, Sentana Rajeg apart from being a wife also works in the livelihood sector that generates money and has an important value in contributing to forming collective assets. This paper is expected to be useful theoretically for the repertoire of legal knowledge, and in practical terms it is expected to provide input to the government and Balinese indigenous peoples in solving problems related to Sentana Rajeg.Key Word: Sentana rajeg; joint property.